Supervised Group Exercise in Axial Spondyloarthritis: Patients' Satisfaction and Perspective on Evidence‐Based Enhancements. Issue 6 (25th April 2020) - Hilberdink, Bas; van der Giesen, Florus; Vliet Vlieland, Thea; van Gaalen, Floris; van Weely, Salima
Abstract : Objective: Supervised group exercise (SGE) has been proven effective in patients with axial spondyloarthritis (SpA), but its contents and dosage do not always comply with current scientific insight. This aim of this study was to describe axial SpA patients' satisfaction with current SGE and perspective on potential evidence‐based SGE enhancements. Methods: Patients with axial SpA who participated in SGE in 4 regions in The Netherlands (n = 118) completed a cross‐sectional survey on their satisfaction with features of their current SGE (8 questions scored on a 3‐point Likert scale; 1 overall grade, scored according to an 11‐point scale) and their perspective on the introduction of appropriately dosed cardiorespiratory and strengthening exercise, monitoring of exercise intensity, periodic reassessments, patient education, and supervision by physical therapists with specific expertise (4 dichotomous questions and one 5‐point Likert scale). Results: Most patients were satisfied with the current total intensity (84 of 112 patients [75%]), duration (93 of 111 patients [84%]), and load (89 of 117 patients [76%]) of the program and the proportion of mobility (102 of 114 patients [90%]), strengthening (90 of 115 patients [78%]), and cardiorespiratory exercise (82 of 114 patients [72%]). The median overall grade of the program was a 7 (interquartile range 7–8). Most patients agreed with the implementation of more frequent (home) exercise (73 of 117 patients [62%]), heart‐rate monitoring (97 of 117 patients [83%]), and annual reassessments (97 of 118 patients [82%]), whereas 50% agreed with the introduction of patient education (37 of 74 patients). The majority found supervision by therapists specializing in axial SpA to be of high importance (105 of 118 patients [89%]). Conclusion: The majority of SGE participants with axial SpA were satisfied with current SGE but also agreed with enhancements in line with scientific evidence. Current satisfaction levels indicate that a planned implementation strategy, including education and addressing potential barriers and facilitators for the uptake of enhancements, is warranted.